2022
DOI: 10.1093/pubmed/fdac008
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic outbreak on mental health of the hospital front-line healthcare workers in Chile: a difference-in-differences approach

Abstract: Background Most of the evidence about impact of COVID-19 pandemic on the mental health of healthcare workers (HCWs) comes from symptom questionnaires. It is important to evaluate main mental health diagnoses in hospital front-line HCW’s during the early acute phase of the COVID-19 pandemic in Chile. Methods An individual-level cross-sectional study using administrative data was conducted. A Difference-in-Difference (DiD) appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(10 reference statements)
0
5
0
3
Order By: Relevance
“…with PPE, during extended working periods, with changes in the organization of work), and faced with insu cient or inadequate coping strategies or resilience (30)(31)(32)(33)(34), impacted their physical health with reports of PPE related skin injuries and headaches or sleep disturbances. All these factors negatively impacted the performance of HCW, leading, for instance to absenteeism (35), nancial problems (that backlashed on mental health) (36) and inevitably resulted in regret about choosing the profession or even intention to resign or change career (37-39) (REF of other LSR).…”
Section: Resultsmentioning
confidence: 99%
“…with PPE, during extended working periods, with changes in the organization of work), and faced with insu cient or inadequate coping strategies or resilience (30)(31)(32)(33)(34), impacted their physical health with reports of PPE related skin injuries and headaches or sleep disturbances. All these factors negatively impacted the performance of HCW, leading, for instance to absenteeism (35), nancial problems (that backlashed on mental health) (36) and inevitably resulted in regret about choosing the profession or even intention to resign or change career (37-39) (REF of other LSR).…”
Section: Resultsmentioning
confidence: 99%
“…Since the emergence of a coronavirus disease in December 2019, healthcare workers have been bearing more serious work and psychological burdens, which has brought great challenges to the health of medical staff ( 37 , 38 ). Several previous investigations have suggested that mental health issues have shown a rapid increase among frontline healthcare workers during the COVID-19 pandemic, including anxiety, depression, emotional exhaustion, PTSD ( 39 , 40 ). This study focused on the emotional and mental threats faced by frontline healthcare workers during the period following their deployment to fight COVID-19 in Wuhan, China.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, Olivares-Tirado e colaboradora evidenciaram que, no registro de licenças médicas da Saúde Privada do Chile, no período pré-pandemia a prevalência de depressão, ansiedade e TEPT em profissionais da saúde foram de 4,6%, 3,8% e 5,9%, respectivamente, enquanto durante a pandemia as taxas aumentaram para 5,2% de depressão, 5,4% de ansiedade e 8,2% de TEPT. Acredita-se que os profissionais de saúde da linha de frente sejam os mais afetados devido à natureza e condições de trabalho estressantes e sustentadas, representando maior risco à saúde mental desses indivíduos 4 .…”
Section: Impacto Na Saúde Mental Dos Profissionais De Saúdeunclassified
“…Devido a sua imprevisibilidade e grande capacidade de infecção, a COVID-19 tem o potencial de causar profundo impacto psicológico 7 , fato igualmente relatado em outras epidemias ao redor do mundo, como a epidemia da síndrome respiratória aguda grave (SARS), em que indivíduos que experimentaram a quarentena cursaram com aumento dos sintomas de depressão e transtorno de estresse pós-traumático (TEPT) 8 . Relatos sobre impactos na saúde mental de epidemias graves prévias concentram-se em indivíduos mais afetados pela doença, como os sobreviventes, amigos, familiares e profissionais de saúde 4 .…”
Section: Introductionunclassified